POLA DINAMIS DISTRIBUSI BERAS UNTUK OPERASI PASAR DOlOG BENGKUlU - Nufus, Nurhayatin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2006)
This research aimed to analyze the moving average of rice distribution and the effect of four decompositon components for market operation along 1995 - 2001 period. The results show that dinamic distribution pattern based on syclicaJ trend tends to increasing along with consumption. There were two clearly variations first quarter / and IV with higher distribution index and quarter 1/ and III with lower index. Under quarter I and IV known as deficit the planting season, while quarter 1/ and III known as harvest season where as the people has plenty of stock in cyl/os. Finally the random component (/) was iffluenced much to the distribution pattern,it was relevance to goverment policy to ruie the rice policy and distrbution.